Synthesis, Antimicrobial, Anti-Virulence and Anticancer Evaluation of New 5(4H)-Oxazolone-Based Sulfonamides - Ahmad J. Almalki; Tarek S. Ibrahim; Ehab S. Taher; Mamdouh F. A. Mohamed; Mahmoud Youns; Wael A. H. Hegazy; Amany M. M. Al-Mahmoudy (Molecules, 2022)
Since the synthesis of prontosil the first prodrug shares their chemical moiety, sulfonamides exhibit diverse modes of actions to serve as antimicrobials, diuretics, antidiabetics, and other clinical applications. This inspiring chemical nucleus has promoted several research groups to investigate the synthesis of new members exploring new clinical applications. In this study, a novel series of 5(4H)-oxazolone-based-sulfonamides (OBS) 9a–k were synthesized, and their antibacterial and antifungal activities were evaluated against a wide range of Gram-positive and -negative bacteria and fungi. Most of the tested compounds exhibited promising antibacterial activity against both Gram-positive and -negative bacteria particularly OBS 9b and 9f. Meanwhile, compound 9h showed the most potent antifungal activity. Moreover, the OBS 9a, 9b, and 9f that inhibited the bacterial growth at the lowest concentrations were subjected to further evaluation for their anti-virulence activities against Pseudomonas aeruginosa and Staphylococcus aureus. Interestingly, the three tested compounds reduced the biofilm formation and diminished the production of virulence factors in both P. aeruginosa and S. aureus. Bacteria use a signaling system, quorum sensing (QS), to regulate their virulence. In this context, in silico study has been conducted to assess the ability of OBS to compete with the QS receptors. The tested OBS showed marked ability to bind and hinder QS receptors, indicating that anti-virulence activities of OBS could be due to blocking QS, the system that controls the bacterial virulence. Furthermore, anticancer activity has been further performed for such derivatives. The OBS compounds showed variable anti-tumor activities, specifically 9a, 9b, 9f and 9k, against different cancer lines. Conclusively, the OBS compounds can serve as antimicrobials, anti-virulence and anti-tumor agents.